SIMULASI HORIZONTAL AXIS WATER TURBINE TIPE SAVONIUS PADA ALIRAN AIR DALAM PIPA MENGGUNAKAN APLIKASI SOLID WORK - Alpriza Sakti Kusuma Putra; Syamsul Hadi; Dominicus Danardono Dwi Prija Tjahjana (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2016)
The potential energy available in the abundant water in Indonesia can be used as electrical energy resources such as pico hydro. Savonius turbines installed at picohydro power plant contained in the flow of water in the pipe. This study uses a turbine that has angle of attack of 80°, 90°, 100°, 110°, the blade number of 2, 4, 6, 8, and blocking angle system of 20°, 30°, 40° and 50°. SolidWorks software is used to perform modeling and simulation in the Savonius turbine. Computational Fluid Design (CFD) is used to design analysis of the turbine. The obtained results are pressure distribution on the Savonius turbine blade, water flow and torque generated. The aims of this study are to obtain the best performance of the turbine design as pico hydro power plants (PLTPH). The results show that the blade number of 2 with the angle of attack about 80° and deflector angle of 50° have the highest torque about 1,766 Nm. Keywords: Savonius turbine, variation, torque, simulation, SolidWorks fluid flow